KEMAMPUAN MULTIPEL REPRESENTASI MATEMATIS MENGGUNAKAN PENDEKATAN MATEMATIKA REALISTIK (PMR) PADA MATERI PECAHAN - Wahid Umar; Pamuti Pamuti (EDUKASI, 2022)
This research is focused on elementary school students multiple mathematical representations through realistic mathematics education on fractions lesson. The problem that will be solved is "what is the ability of multiple mathematical representations of fourth grade elementary school students through realistic mathematics education on the concept of fractions and equivalent fractions?" This research was conducted at public school 1 Ternate City. The research subjects were 4 students, one high-ranking student, two medium-ranking students, and one low-ranking student. The research was conducted in two learning actions. The results of data analysis found: (1) high-ranking students (S1), from the beginning of first action to the end of second action, liked to study in groups. In the first action the percentage of mathematical representation ability to the ideal maximum score is 100% both when working on the LKPD and in the final test of first action. The mode of representation ability level is at level 4 (creating and using representations correctly); (2) students of moderate rank (S2 and S3), enjoy working in groups. The average percentage of achievement of the mathematical representation ability score by masters working on the LKPD is 94% and at the end of the action test it is 100%. The percentage of achievement of the mathematical representation ability score by S3 doing LKPD is 99.5% and at the end of the action test is 96%. S2 and S3 mathematical representation ability level mode is at level 4; (3) low-ranking students (S4) who like to work alone. The average percentage of achievement scores of mathematical representation abilities by S4 working on LKPD is 72% and on the final test of action 78%; (4) students enjoy learning the concept of fractions and equivalent fractions through realistic mathematics education. The use of bread model props for the concept of fractions and or equivalent fractions makes students actively work in pairs and enjoy learning; (5) students are able to use props to solve problems, (6) students are able to manipulate images to solve problems.